2019
DOI: 10.33988/auvfd.423491
|View full text |Cite
|
Sign up to set email alerts
|

The effect of olive leaf extract on digestive enzyme inhibition and insulin production in streptozotocin-induced diabetic rats

Abstract: Olive leaf has natural bioactive compounds, mainly oleuropein, that are widely considered to have potentially beneficial effects on health. This study aimed to evaluate the effects of olive leaf extract (OLE) on the inhibition of carbohydrate digestive enzymes, and immunohistochemical study of insulin in the pancreas of in vivo streptozotocin-induced diabetic rats. Blood glucose levels, insulin, glycated hemoglobin (HbA1c), α-amylase and α-glucosidase activities, and an immunohistochemical study were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…e leaf extract is more potent than oleuropein in preventing the cytotoxic effects and only leaf extract preserves GPx [234] In STZ-diabetic male rats, the extract ameliorates diabetic alterations [235] In STZ-diabetic male rats, it decreases glycaemia and HbA1c and increases insulin. It also inhibits α-amylase and α-glucosidase [236] In acellular model, it inhibits DPPH radical generation. In STZ-diabetic male rats, the extract increases CAT activity, GSH and lowers lipid peroxidation, Chol, TG, histological pancreas, and hepatic damage [237] In male alloxan-diabetic rats, it shows a hypoglycemic effect and reduces the damage of islets of langerhans [238] In cultured neonatal rat cardiomyocytes of both sexes, it decreases maximum I (Ca,L) in a reversible manner [239] Male rats fed with a high-fat diet develop signs of metabolic syndrome.…”
Section: Effects Of Evoo Voo Oo Leaf Extracts and Mpcs Onmentioning
confidence: 99%
“…e leaf extract is more potent than oleuropein in preventing the cytotoxic effects and only leaf extract preserves GPx [234] In STZ-diabetic male rats, the extract ameliorates diabetic alterations [235] In STZ-diabetic male rats, it decreases glycaemia and HbA1c and increases insulin. It also inhibits α-amylase and α-glucosidase [236] In acellular model, it inhibits DPPH radical generation. In STZ-diabetic male rats, the extract increases CAT activity, GSH and lowers lipid peroxidation, Chol, TG, histological pancreas, and hepatic damage [237] In male alloxan-diabetic rats, it shows a hypoglycemic effect and reduces the damage of islets of langerhans [238] In cultured neonatal rat cardiomyocytes of both sexes, it decreases maximum I (Ca,L) in a reversible manner [239] Male rats fed with a high-fat diet develop signs of metabolic syndrome.…”
Section: Effects Of Evoo Voo Oo Leaf Extracts and Mpcs Onmentioning
confidence: 99%
“…Phytochemicals in herbs can exert antidiabetic effects through various mechanisms. These mechanisms may be through inhibition of digestive enzymes and/or by acting like insulin-mimetic to reduce postprandial blood glucose (Temiz & Temur, 2019). Besides they might have antidiabetic effects such as reducing glucose absorption in the small intestine, stimulation of insulin secretion from islets, improving insulin sensibility, and increasing the uptake and bioavailability of glucose to the cells (Temiz and Temur, 2019;Temiz, 2021;Yang et al, 2015;Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that several herbs and species, including components of the food supplement (Diapin ® ) used in the present study, exhibit antidiabetic properties. Temiz & Temur (2019) demonstrated that the extract of olive leaves significantly inhibited intestinal α-amylase and α-glucosidase of streptozotocin-induced diabetic rats. In addition, the levels of insulin increased, while those of blood glucose and glycated haemoglobin decreased.…”
Section: Discussionmentioning
confidence: 97%